Analisis Pengendalian Persediaan dengan Menggunakan Metode Probabilistik Continuous Review (S, Q) pada Bahan Baku Baja Scrap ST 37 EX Automotif di PT Pindad - Napitupulu, Theresa Nova; Hilman, Tamadara; Guslan, Darfial (Innovative: Journal Of Social Science Research, 2024)
PT Pindad is a company engaged in the business of manufacturing industry, services and trade of defense, security and industrial products. PT Pindad has several departments, one of which is the Tempa and Cor (TC) department. Tempa and Cor Department (TC) has a warehouse that stores material inventory, one of which is the raw material for Baja Scrao ST 37 EX Automotif which has an overstock problem. The purpose of this study is to determine the optimal amount of inventory and the optimum total cost of inventory on Baja Scrap ST 37 EX Automotif raw materials. This research uses the continuous review method (s, Q). Based on the analysis that has been done, the optimal amount of Baja Scrap ST 37 EX Automotif inventory is obtained with an optimum order quantity (q0) of 66,628.58 kg, reorder point (r) when inventory is 163,911.64 kg, expected inventory shortage in each period (N) of 163.31 kg, and safety stock (SS) of 37,661.65 kg. There is a cost savings of 40.28% of the costs previously incurred by the company. The difference in the two cost calculations between company policy and the continuous review (s, Q) method is IDR 3,929.030.687,25.